Differences in metabonomic profiles of abdominal subcutaneous adipose tissue in women with polycystic ovary syndrome - Di, Fangfang; Gao, Danfeng; Yao, Lihua; Zhang, Runjie; Qiu, Jin; Song, Liwen (Frontiers in Endocrinology, 2023)
Polycystic ovary syndrome (PCOS) is a complex endocrine disorder that often coexists with a metabolic disorder. Studies have demonstrated that the malfunction of adipose tissue, particularly abdominal adipose tissue, could exacerbate reproductive and metabolic problems in PCOS patients. Adipose tissue-secreted signaling mediators (e.g., lipids and metabolites) would then interact with other body organs, including the ovary, to maintain the systemic equilibrium. In this study, we examined adipose samples from PCOS patients and unaffected individuals using a liquid chromatography–mass spectrometry-based metabonomics approach (LC–MS/MS). PCOS biomarkers were selected using multivariate statistical analysis. Our pathway analysis revealed that these differential metabolites could be engaged in inflammatory diseases and mitochondrial beta-oxidation. We further developed an in vitro PCOS cell model to examine the effects of hyperandrogenism on granulosa cells and related metabolic disorders. We noted that isoleucine recovered the promotive effect on cell apoptosis, inhibitory effect on cell proliferation, sex hormone secretion, and mitochondrial function induced by dehydroepiandrosterone. Our gas chromatography–mass spectrometry targeted analysis (GC–MS/MS) revealed that isoleucine was significantly decreased in PCOS patients. Based on these results, we speculate that metabolome alterations are vital in ameliorating PCOS symptoms. This may be a novel therapeutic target for PCOS treatment. Our study provides preliminary evidence that these findings will enhance our ability to accurately diagnose and intervene in PCOS.